The Influence of Turnover Intention, Work Discipline, Work Motivation, and Work Environment on Employee Performance of PT Telexindo Bizmart - Usmeila, Evrida; Asai, Markonah; Suryanto, Suryanto; Cahaya, Yohanes Ferry (Mediastima, 2024)
This study aims to analyze the influence of turnover intention, work discipline, work motivation, and work environment on employee performance at PT Telexindo Bizmart. Using a sample of 150 employees selected through purposive sampling, a quantitative descriptive analysis method with Likert scale measurements were employed. Data were collected using a Google Form questionnaire and analyzed using SPSS 22. The results showed an R square value of 0.708, indicating that 70.8% of employee performance is explained by independent variables, while 29.2% is explained by other variables. Turnover intention had a significant negative effect, while work discipline, work motivation, and work environment had a significant positive effect on employee performance. It is recommended that PT Telexindo Bizmart reduces turnover intention and improves work discipline, work motivation, and work environment to enhance employee performance